Political Party Endorsement in Supporting the Sole Candidate Muhammad Fadhil Arief and H. Bakhtiar in the 2024 Simultaneous Regional Election of Batanghari Regency - Hatta Abdi Muhammad; Sutri Destemi Elsi; Cholillah Suci Pratiwi; Nasuhaidi Nasuhaidi; Arissy Jorgi Sutan (Greenation Research & Yayasan Global Resarch National, 2026)
This study analyzes the political party endorsement strategies leading to the sole-candidate scenario in Batanghari Regency during the 2024 simultaneous regional elections and its implications for democratic quality. While existing literature largely focuses on multi-candidate competition, a significant research gap remains regarding the specific mechanisms of